Combining Strategic and Adaptive Policymaking for Telecommunication. The Way Forward for EU's Connectivity - Francesco Cappelletti; Erik Bohlin (International Telecommunications Society (ITS), 2024)
The European Union's attention to telecommunications and its infrastructure has increased over the past years. This invigorated approach highlights the need for adaptive policymaking to keep pace with technological advancements and market dynamics towards a unified European telecom market. This paper examines the concept of strategic legislation, emphasizing the need for adaptive, flexible, and forward-looking policies. It discusses the advantages of an adaptive and proactive legislative approach, which can enable the telecommunication sector to keep pace with and influence market dynamics and technology integration. With the digital landscape evolving faster than traditional policy cycles can adapt, this work advocates for a dynamic approach that integrates flexibility and responsiveness into EU telecommunications policy. This approach is identified as crucial for fostering a competitive landscape, encouraging innovation, and attracting investment.
Keywords: 330; Adaptive Policymaking; Strategic Legislation; EU; Telecommunication; Technological Advancement